The British Empire - Wiszniowska-Majchrzyk, Marta; Miksza, Agnieszka; Bednarek, Zbigniew; Jan Korporowicz, Łukasz; Kalinowska, Anna; Zinkiewicz, Grzegorz; Sosnowska, Monika; Plesiewicz-Świerczyńska, Izabela; Łukowska, Maria; Deles, Przemysław (Wydawnictwo Uniwersytetu Łódzkiego, 2025)
'Although the phrase “the empire on which the sun never sets” was originally used by Charles V of the House of Habsburg to refer to the beginnings of Spanish colonial expansion